2012
DOI: 10.1007/s11434-012-5411-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and biodegradation of polycyclic aromatic hydrocarbons by Phanerochaete chrysosporium in aqueous solution

Abstract: Biosorption and biodegradation of phenanthrene and pyrene by live and heat-killed Phanerochaete chrysosporium are investigated to elucidate the bio-dissipation mechanisms of polycyclic aromatic hydrocarbons (PAHs) in aqueous solution and its regulating factors. The effects of nutrient conditions (carbon source and nitrogen source concentrations), the co-existing Cu 2+ , and repeated-batch feed of PAHs on the biosorption and biodegradation are systematically studied. The removal of PAHs by dead bodies of P. chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The adsorption of n -hexadecane by heat-killed microbial strain was a fast process, however, with the time increasing, the adsorbed n -hexadecane were released from dead bacterial strain. This phenomena was also obtained from the bioadsorption behavior of microbial cell for PAHs and alkane which was controlled by the distributional effects with the process of sorption-desorption being reversible133031. Rosenberg and Rosenberg32 had shown that the rate of hydrocarbon degradation by bacterial cells was dependent on cell affinity.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The adsorption of n -hexadecane by heat-killed microbial strain was a fast process, however, with the time increasing, the adsorbed n -hexadecane were released from dead bacterial strain. This phenomena was also obtained from the bioadsorption behavior of microbial cell for PAHs and alkane which was controlled by the distributional effects with the process of sorption-desorption being reversible133031. Rosenberg and Rosenberg32 had shown that the rate of hydrocarbon degradation by bacterial cells was dependent on cell affinity.…”
Section: Resultsmentioning
confidence: 93%
“…The concentrations of n -hexadecane that washed solution by this extraction process were considered as the surface adsorption contents by a microbial consortium133031. Samples were measured the concentration of n -hexadecane at day 1, 2, 3, 4, 5, 6, 7 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…() observed that bioadsorption of heat‐killed cells was related to carbon‐normalized partition coefficients. Ding, Chen, and Zhu () explored the respective partition coefficients of PHE and PYR and pointed out that removal of PAHs by heat‐killed bodies of Phanerochaete chrysosporium was only attributed to the mechanism of bioadsorption. These findings indicated the rapid adsorption of PHs by heat‐killed mycelial pellets.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Boonchan et al (2000), Acevedo et al (2011), andDing et al (2013) have used successfully white-rot fungi in the biodegradation of PAHs. Some others have demonstrated the efficiency of these fungal group in biodegradation of petroleum derivatives in the environment (Ting et al, 2011;Yanto and Tachibana, 2014;Khan et al, 2015).…”
Section: Evaluation Of Fungal Bioaugmentation and The Removal Of Petrmentioning
confidence: 99%